METODE PENGGALIAN INFORMASI DALAM ANALISIS PEMBIAYAAN PADA BANK MUAMALAT INDONESIA CABANG MALANG - Nugraha, Bagus Aji; Triyuwono, Iwan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
The purpose of this research is to explain the method of information gathering on a financing analysis in Bank Muamalat Indonesia, Malang branch. This research is a qualitative research with a case study approach, conducted in Bank Muamalat Indonesia, Malang Branch. The technique of data collection was done by interview, observation and documentation. Interview conducted to both of Relationship Financing Manager which is officer and non-officer. Observations made on Relationship Financing Manager related to the analysis performed on the financing applicant and filing requirements documents owned by the financing applicant. Documentation conducted related to for financing handling procedures and Financing Proposal Memorandum. Results of this study indicate that the method of how Relationship Financing Manager collect the information needed-to analyze a financing in Islamic banks-is started by determine what relevant information to be obtained. Then find any possible method in such a way to get the information, such as: interview, survey, through the required documents, through BI Checking and taksator warranty. So far, by using the financing handling process and existing method, is quite effective. It can be seen from financing problems records in Bank Muamalat, Malang Branch, basically is extremely rare. Keywords: financing analysis, Relationship Financing Manager, method of information gathers